2020
DOI: 10.12691/ajmcr-8-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the Mitral-Aortic Fibrosa in the Absence of Valvulitis

Abstract: The mitral-aortic intervalvular fibrosa (MAIVF) is the thin avascular fibrous structure located between the left side of the non-coronary cusp, the left coronary cusp and the anterior mitral leaflet. MAIVF pseudoaneurysm typically results as a complication of endocarditis, aortic valve surgery or chest trauma. We present a case of an incidental MAIF pseudoaneurysm in a 68-year female with a history of rheumatic fever without involvement of the mitral apparatus. We also discuss the presentation, evaluation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Additionally, AR and BAV were described as other causal factors. Chandrakumar et al [9] reported P-MAIVF without valvulitis as a rare case. Recently, Spampinato et al [10] reported P-MAIVF after minimally invasive mitral valve repair.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AR and BAV were described as other causal factors. Chandrakumar et al [9] reported P-MAIVF without valvulitis as a rare case. Recently, Spampinato et al [10] reported P-MAIVF after minimally invasive mitral valve repair.…”
Section: Discussionmentioning
confidence: 99%